English language speaking anxiety among students from two public universities in Sarawak / Sandra Phek Lin Sim, Jiin Yih Yeo, Kimberley Yih Long Lau - Phek Lin Sim, Sandra; Yih Yeo, Jiin; Yih Long Lau, Kimberley (Universiti Teknologi MARA Cawangan Sarawak, 2020)
This quantitative research studied the anxiety level of university students towards speaking English as a second language (ESL) to examine whether there is any correlation between the university students’ ESL speaking anxiety and the demographic factors such as the SPM English results, mother tongue, and parents’ academic qualifications. A sample of 592 students was randomly selected from two public universities in Sarawak, Malaysia. Items in the PSCAS questionnaire by Yaikhong and Usaha (2012) were adapted to measure the students’ anxiety level in speaking English. Data were analysed using descriptive statistics to identify the students’ anxiety level in speaking English. Inferential statistics (Pearson correlation) was used to examine the relationship between the university students’ ESL speaking anxiety and demographic factors. The findings indicate that these students experienced a moderate level of speaking anxiety. There was a positive correlation between the university students’ ESL speaking anxiety and SPM English Language results. Nevertheless, there was a low negative correlation between the students’ ESL speaking anxiety and mother tongue as well as parents’ academic qualifications. Findings from this study provide a basis for educators to plan effective teaching strategies to reduce English speaking anxiety among university students.